Pengaruh Kompetensi dan Gaya Kepemimpinan Transformasional Terhadap Kinerja Aparatur Sipil Negara (ASN) dengan Core Values Berakhlak sebagai Variable Intervening - Yuli Setyaningrum; Joko Utomo; Kertati Sumekar (Pusat Riset dan Inovasi Nasional, 2026)
This study study to analyze the influence of competence and transformational leadership style on the performance of Civil Servants (ASN), with the BerAKHLAK Core Values as an intervening variable (A Case Study at the Department of Transportation, Jepara Regency). This is a quantitative study with an explanatory level of analysis. The research design follows a causal pattern. The population consists of 197 civil servants at the Jepara Regency Department of Transportation, with the sample selected using proportional random sampling, resulting in 122 respondents. Data were collected using questionnaires. The data were analyzed descriptively and quantitatively using Structural Equation Modeling (SEM). The theoretical findings and implications of this study are as follows: ASN competence has a positive and significant effect on performance; transformational leadership style has a positive and significant effect on performance; ASN competence positively influences the internalization of the BerAKHLAK Core Values; transformational leadership style significantly affects the BerAKHLAK Core Values; the BerAKHLAK Core Values significantly influence ASN performance; the BerAKHLAK Core Values act as a mediating variable in the relationship between competence and ASN performance; and the BerAKHLAK Core Values mediate the influence of transformational leadership style on ASN performance